Exercise attenuates levodopa-induced dyskinesia in 6-hydroxydopamine-lesioned mice - Jr., A. S. Aguiar (2013)
l-DOPA alleviates the motor symptoms of Parkinson’s disease, but its long-term use is associated with undesirable dyskinesia. We now tested whether exercise can attenuate this l-DOPA-induced dyskinesia (LID). We tested the effects of exercise on LID in 6-hydroxydopamine hydrochloride-hemiparkinsonian mice. Animals were treated with l-DOPA/benserazide (25/12.5 mg/kg, i.p.) without and with possibility to exercise (running wheel) during 2 weeks. Exercise drastically prevented the development of LID, and its associated aberrant striatal signaling, namely the hyperphosphorylation of dopamine and cAMP-regulated phosphoprotein 32 kDa protein and c-Fos expression. Our results indicate that exercise can partially prevent the development of LID through the normalization of striatopallidal dopaminergic signaling.